EVALUATING SESAME LIGNANS FROM SESAME SEEDS (SESAMUM INDICUM L.): UNVEILING ANTIDEPRESSANT AND COGNITIVE ENHANCEMENT POTENTIAL THROUGH IN SILICO MOLECULAR DOCKING AND IN VITRO STUDIES - ARUNA PRIYADHARSHINI M; PUNNAGAI KUMARAVELU; BHUVANESWARI; ARAVINDKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objective: Sesame lignans, sesamin and sesamolin, have shown promise due to their anti-inflammatory and antioxidant properties, but their precise neuropharmacological mechanisms and safety profiles remain inadequately explored. The study was purposed to “Evaluating Sesame Lignans from Sesame Seeds (Sesamum indicum L.): Unveiling antidepressant and cognitive enhancement potential through in silico molecular docking and in vitro studies.” Method: This study employed an integrated in silico and in vitro approach. Molecular docking was performed to evaluate the binding affinity and interactions of sesamin and sesamolin with targets – amyloid-beta (Aβ), apolipoprotein E, and the norepinephrine transporter (NET). Pharmacokinetic and toxicity profiles were predicted using Swiss absorption, distribution, metabolism, and excretion, Pharmacokinetics using graph-based signatures (pkCSM), and Protein Toxicity Prediction System – Version II (ProTox-II). In vitro cytotoxicity was assessed in SH-SY5Y neuroblastoma cells using the MTT assay (- 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide Assay). Result: Both lignans exhibited strong binding affinities for Aβ and NET, forming stable interactions via hydrogen bonds and hydrophobic contacts. They demonstrated favorable drug-likeness, high gastrointestinal absorption, and blood-brain barrier permeability. In silico predictions indicated a low toxicity risk, with no mutagenic or carcinogenic effects. Crucially, both compounds maintained high cell viability (>70%) in SH-SY5Y cells at concentrations up to 200 μg/mL, with half-maximal inhibitory concentration values of 386 μg/mL (sesamin) and 361 μg/mL (sesamolin), confirming their neuronal safety. Conclusion: Sesamin and sesamolin demonstrate significant potential as multi-target neurotherapeutic agents. Their ability to modulate key pathological targets, combined with excellent pharmacokinetic properties and a high margin of neuronal safety, positions them as promising candidates for the treatment of cognitive disorders and depression, warranting further preclinical investigation.